Higgins 2009. English as a Local Language - Lusekelo, Amani (AAeO - Afrikanistik-Aegyptologie-Online, 2009)
Christina Higgins 2009. English as a Local Language: Post-colonial Identities and Multilingual Practices. Bristol: Multilingual Matters Ltd. 176 Pages, ISBN: 9781847691804, £ 19.95